Central bank digital currency and transmission of monetary policy - Saroj Bhattarai; Seyed Mohammadreza Davoodalhosseini; Zhenning Zhao (Bank of Canada, 2024)
How does the transmission of monetary policy change when a central bank digital currency (CBDC) is introduced in the economy? Do aspects of CBDC design, such as how substitutable it is with bank deposits and whether it is interest bearing, matter? We study these questions in a general equilibrium model with nominal rigidities, liquidity frictions, and a banking sector where commercial banks face a leverage constraint. In the model, CBDC and commercial bank deposits can be used as a means of payments, and they provide liquidity services to households. Banks issue deposits and extend loans to firms, and bank deposits are backed by loans and central bank reserves. We find that the effects of a canonical monetary policy shock, a shock to the Taylor rule that governs interest on central bank reserves, is magnified with the introduction of a fixed-interest-rate CBDC. More generally, whether CBDC magnifies or abates the response of the economy depends on the type of shock (e.g., interest rate or quantity of reserves shock). We also find that the response of the economy depends on the monetary policy framework-whether the central bank implements monetary policy through reserves or through CBDC-as well as central bank balance sheet rules that govern the quantity of CBDC and reserves
Keywords: E31; E4; E50; E58; G21; G51; 330; Digital currencies and fintech; Monetary policy; Monetary policy framework; Monetary policy transmission; Interest rates